Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.